KONSANTRİK TİP BİR ISI DEĞİŞTİRİCİSİNDE ISI TRANSFERİNİN DENEYSEL VE SAYISAL OLARAK İNCELENMESİ - BUDAK, NEŞE (Fırat Üniveristesi, 2011)
Bu çalışmada konsantrik tip ( iç içe ) bir ısı değiştiricide iç borunun girişine yerleştirilen dört farklı tipteki türbülatörlerin ısı transferine etkisi deneysel ve sayısal olarak araştırılmıştır. Bu amaçla kurulan deneysel sistemde ısı değiştiricinin iç borusundan sıcak akışkan olarak hava, soğuk akışkan olarak dış borusundan su geçmektedir. Deliksiz ve delik konumları farklı olarak imal edilen türbülatörlerin ısı transferi ve basınç düşüşüne etkisini araştırmak üzere aynı ve zıt yönlü paralel akış şartlarında deneyler yapılmıştır. Sistemin ekserji analizi yapılmıştır.Sayısal çalışmada sonlu hacimler metoduna dayalı bir bilgisayar programı olan ANSYS Fluent kod programı kullanılarak temel korunum denklemleri sürekli rejimde, üç boyutlu ve türbülanslı akış şartlarında çözülmüştür. Havanın farklı debi değerlerinde ( 7, 8, 9, 10, 11 ve 12 m3/saat ) yapılan sayısal analiz sonuçları elde edilmiştir. Yapılan sayısal analizler sonucunda sıcaklık, hız ve basınç dağılımları gösterilmiştir.Deneysel ve sayısal sonuçlar karşılaştırılmış ve birbirleriyle uyum içerisinde olduğu görülmüştür. Analizlerden elde edilen veriler incelendiğinde en fazla ısı transferi iç, dış kanadı ve gövdesi delikli türbülatörde olduğu görülmüştür.

In this study, the effect of four different types of turbulators placed inside the pipe entrance in a concentric (nested) heat exchanger on heat transfer and pressure drop has been investigated experimentally and numerically. For this purpose, an experimental system of heat exchanger was established in which air passed through the inner tube as hot fluid whereas water passed through the outer pipe as cold fluid. Some experiments have been conducted under the same and opposite directional parallel flow conditions in order to investigate the effect of turbulators that are produced as unperforated and perforated in different positions on heat transfer. Exergy analysis of system has been made.The basic governing equations have been solved under steady-state, three-dimensional and turbulent flow conditions using ANSYS Fluent code program which is a computer program based on finite volume method in numerical study. Different levels of air flow ( 7, 8, 9, 10, 11 and 12 m3/h ) have been obtained from the results of numerical analysis. Also, temperature, velocity and pressure distributions have been obtained as a result of the numerical analysis.Experimental and numerical results have been compared and found to be in harmony with each other. When the research data was analysed, it became clear that maximum heat transfer happens in the inner, outer wing and body perforated turbulators.
Experimental and numerical investigation of heat transfer in a concentric heat exchanger
Keywords: Makine Mühendisliği